1998
DOI: 10.1002/(sici)1096-9861(19981130)401:4<437::aid-cne2>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Periaqueductal gray matter projection to the parabrachial nucleus in rat

Abstract: The efferent projections from the periaqueductal gray matter (PAG) to the parabrachial nucleus (PB) were studied in the rat following microinjections of the anterograde axonal tracer Phaseolus vulgaris-leucoagglutinin (PHA-L) into restricted regions of the PAG. The dorsomedial and dorsolateral PAG columns project almost exclusively to the superior lateral PB subnucleus, whereas the lateral and ventrolateral PAG columns project to five lateral PB sites: dorsal lateral subnucleus, medial and lateral crescent are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 65 publications
3
50
0
Order By: Relevance
“…Current evidence suggests that dorsolateral pontine-evoked modulation of the arterial baroreflex primarily originates from the ventrolateral regions of the LPBN and involves descending projections to both the NTS (9,24) and the RVLM (24)(25)(26)31). Yet, neuroanatomical data suggest that there are few direct projections from the dorsal PAG to the ventrolateral PBN (23). Instead, descending projections from the dorsal PAG primarily terminate in the central and superior lateral regions of the LPBN.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Current evidence suggests that dorsolateral pontine-evoked modulation of the arterial baroreflex primarily originates from the ventrolateral regions of the LPBN and involves descending projections to both the NTS (9,24) and the RVLM (24)(25)(26)31). Yet, neuroanatomical data suggest that there are few direct projections from the dorsal PAG to the ventrolateral PBN (23). Instead, descending projections from the dorsal PAG primarily terminate in the central and superior lateral regions of the LPBN.…”
Section: Introductionsupporting
confidence: 83%
“…In a more recent study from our lab, utilizing smaller microinjection volumes, we confirmed that activation of lateral PBN (LPBN) neurons was essential for dorsal PAG evoked increases in MAP and heart rate (HR), as well as changes in breath timing (16). This observation corroborated neuroanatomical data showing that dorsal PAG neurons primarily project to the LPBN and not the medial PBN (23). Unexpectedly however, we demonstrated that bilateral blockade of LPBN area neurons with the GABA-A receptor agonist muscimol or the glutamate receptor antagonist kynurenic acid was approximately 20% more effective at attenuating dorsal PAG evoked increases in HR than changes in MAP.…”
Section: Introductionmentioning
confidence: 99%
“…The thalamus is crucial in relaying nociceptive information via the ascending pain pathways and further projects onto the cortical regions which are involved in pain perception and emotional pain processing. The spinoparabrachial pathway is involved in the cognitive-affective dimension of pain as these neurons from the dorsal horn of the spinal cord project onto the parabrachial area, where they form synaptic connections with third order neurons that terminate in the ventral medial nucleus of the hypothalamus and the central nucleus of the amygdala (Bester et al, 1997;Derbyshire et al, 1997;Krout et al, 1998). The spinothalamic tract plays an important role in sympathetic and motivational responses to pain, as it projects onto the parabrachial nucleus and the PAG via the spinomesencephalic tract (Allen and Pronych, 1997;Jatsu Azkue et al, 1997;Keay et al, 1997).…”
Section: Ascending Pain Pathwaysmentioning
confidence: 99%
“…The spinothalamic tract plays an important role in sympathetic and motivational responses to pain, as it projects onto the parabrachial nucleus and the PAG via the spinomesencephalic tract (Allen and Pronych, 1997;Jatsu Azkue et al, 1997;Keay et al, 1997). The PAG functions as a behavioural state-dependent relay station for modulation of both the descending and ascending pain pathways (Krout et al, 1998), and it also projects to the parabrachial nucleus which is known to be involved in emotional response to pain (Hunt and Mantyh, 2001;Lovick, 1996;Lumb and Lovick, 1993). …”
Section: Ascending Pain Pathwaysmentioning
confidence: 99%
“…These include the lateral reticular formation, periaqueductal gray matter, and spinal trigeminal nucleus. All are innervated by spinal afferents, activated by noxious stimulation, and project to LPB (Cechetto et al, 1985;McMahon and Wall, 1985;Milner and Pickel, 1986;Herbert et al, 1990;Lanteri-Minet et al, 1994;Bernard et al, 1995;Craig, 1995;Feil and Herbert, 1995;Krout et al, 1998;Imbe et al, 1999;Keay and Bandler, 2002). However, it is not clear whether these projections contain substance P.…”
Section: Nociceptive Afferent Pathways To the Lateral Parabrachial Numentioning
confidence: 99%